Epiphytic bacterial community composition on four submerged macrophytes in different regions of Taihu Lake - Fang, Hongda; Zhen, Zhuo; Yang, Fan; Su, Hailei; Wei, Yuan (Frontiers in Plant Science, 2024)
The epiphytic bacteria in aquatic ecosystems, inhabiting a unique ecological niche with significant ecological function, have long been the subject of attention.Habitat characteristics and plants species are believed to be important in controlling the assembly of epiphytic bacteria. However, the underlying principle governing assembly of the epiphytic bacterial community on macrophytes is far from clear. In this study, we systematically compared the diversity and community composition of epiphytic bacteria both in different habitats and on different species of macrophytes where they were attached on. Results suggested that neither the plant species nor the habitat had a significant effect on the diversity and community of epiphytic bacteria independently, indicating that the epiphytic bacterial community composition was correlated to both geographical distance and individual species of macrophytes. Besides, almost all of the